1999
DOI: 10.1177/109442819922004
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Variance Approach to Content Validation

Abstract: Although procedures for assessing content validity have been widely publicized for many years, Hinkin noted that there continue to be problems with the content validity of measures used in organizational research. Anderson and Gerbing, and Schriesheim, Powers, Scandura, Gardiner, and Lankau discussed the problems associated with typical content validity assessment and presented techniques that can be used to assess the empirical distinctiveness of a set of survey items. This article reviews these techniques an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
413
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(440 citation statements)
references
References 12 publications
14
413
1
Order By: Relevance
“…In this case, this study followed Hinkin's procedure (Hinkin, 1995;Hinkin & Tracey, 1999). The procedure is composed of the following three steps: (1) content validity assessment, (2) item reduction, and (3) confirmatory factor analysis.…”
Section: Scale Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, this study followed Hinkin's procedure (Hinkin, 1995;Hinkin & Tracey, 1999). The procedure is composed of the following three steps: (1) content validity assessment, (2) item reduction, and (3) confirmatory factor analysis.…”
Section: Scale Developmentmentioning
confidence: 99%
“…The assessment of content validity followed the procedure of Hinkin and Tracey (1999). Respondents first rated each of the 35 AID items according to the extent to which they believed the items were consistent with each of two dimensions' definitions of AID.…”
Section: Scale Developmentmentioning
confidence: 99%
“…Therefore, following a technique developed by Hinkin and Tracey (1999) we conducted a more comprehensive content validity assessment, on a smaller number of leadership scales, using a method that utilizes analysis of variance (ANOVA) to empirically test item distinctiveness. This technique can be used with relatively small sample sizes (Hinkin & Schriesheim, 2008), and has been used previously to investigate the content validity of leadership measures (Hinkin & Schriesheim, 2008).…”
Section: Content Of Leadership Measuresmentioning
confidence: 99%
“…IS professionals must also understand business processes and strategy as well as how people will interact with technology to support those processes [24,25]. Therefore, judging an IS professional's or student's ability to solve unstructured IS problems based only on their self-efficacy with specific technologies would provide only a limited view.…”
Section: Introductionmentioning
confidence: 99%
“…While this line of research has shown promising results for explaining employee productivity, the commonly accepted measure of CreaSE only refers to the general management context and is not well-suited to the unique IS discipline, which requires expertise in a combination of technology, business processes, and human behavior [7,24,25]. Furthermore, there has not been a rigorous scale development and refinement process for this construct in the management discipline based on the strongest principles for scale development [c.f.…”
Section: Introductionmentioning
confidence: 99%